The new encyclopedia británica in 30 volumes, macropedia VOL. 13 / William Benton - Benton, William (1977)
Theological Works, miscellaneous, novels, the history of New Mexico, the natural and human landscape, the people of New Mexico, the state´s economy, administration and social conditions, the growth of the metropolis, the contemporary city, the landscape, the people, the economy, administration and social conditions, cultural life and institutions, career, the history of new York, the natural and human landscape, the people of new York.